SOSIALISASI DAN PEMERIKSAAN GOLONGAN DARAH SISTEM ABO DI KELURAHAN SUKAPURA BANDUNG - Khoirunnisa, Ria (Jurnal Pengabdian Kepada Masyarakat, 2024)
The basis of the ABO system blood group test is to examine the agglutination reaction between agglutinogens on the surface of red blood cells and the same agglutinins in the serum reagent. Urgent problems in several areas include low levels of education, understanding, and knowledge as well as limited facilities and infrastructure for carrying out blood type tests. Therefore, it is important to carry out blood group testing early so that people do not experience delays in handling blood needs in medical conditions that allow blood transfusions. This community service activity aims to provide understanding and increase residents’ knowledge regarding ABO blood group types, as well as facilitating residents to find out their blood type through blood group testing. The methods used were lectures and questions and answers as well as experiments related to socialization and blood group testing. In the blood group test in RW 01 Sukapura Village, data was obtained that 52% had blood type A, 26% had blood type B, 16% had blood type O, and 6% had blood type AB. In this community service activity, there was an increase in the knowledge of RW 01 Sukapura Village residents regarding the ABO blood group system and residents were facilitated to find out their blood group type through a blood group test. Keywords: agglutinin; agglutinogen; blood type; community service; ABO system.